2006
DOI: 10.1002/app.25249
|View full text |Cite
|
Sign up to set email alerts
|

Cation exchange finishing of nonwoven polyester with polycarboxylic acids and cyclodextrins

Abstract: We describe a chemical method for the finishing of polyester nonwoven fabrics that aimed to obtain ion exchange textiles. This approach was based on the use of polycarboxylic acids (PCA) and cyclodextrins as carbohydrate compounds and finishing agents, respectively. It was observed that the reaction between these reactants yielded a crosslinked polymer that was physically anchored onto the fibers. This polymer can be considered as a resin issued from the esterification between the COOH groups of the PCA with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Besides, bCD is a cyclic polysaccharide, with a high number of hydroxyl groups and its rigidity is favorable for a good and stable grafting ratio via esterification with PCA. A previous comparison demonstrated that bCD as polyol was more appropriate than starch (linear polysaccharide) in term of free carboxylic functions in the frame of this study [7]. Finally, the preparation used is simple (one step), ecologic (water as reaction medium) and of very low cost, and so in agreement with remediation technics.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Besides, bCD is a cyclic polysaccharide, with a high number of hydroxyl groups and its rigidity is favorable for a good and stable grafting ratio via esterification with PCA. A previous comparison demonstrated that bCD as polyol was more appropriate than starch (linear polysaccharide) in term of free carboxylic functions in the frame of this study [7]. Finally, the preparation used is simple (one step), ecologic (water as reaction medium) and of very low cost, and so in agreement with remediation technics.…”
Section: Introductionmentioning
confidence: 53%
“…1A). The description of the synthesis was developed in a previous paper [7]. The reaction consisted of a crosslinking polycondensation between a PCA and a bCD mixture previously impregnated onto the fabric in a padding step.…”
Section: Cationic Exchange Textiles (Cet)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this cyclodextrin polymer layer could act as a degradable diffusion barrier for the guest drug molecules and sustain the drug release. Besides, the macromolecular structure of the poly(BTCA-HPbCD) applied in the present study also supports carboxylate groups that are capable of forming complementary interactions to cavities with the drugs, through acid-base interactions [34]. For that reason, biomaterials devices functionalized with this type of CD polymers can interfere through specific (inclusion complexes) and nonspecific interactions (acid-base, hydrogen bonding) with the drugs.…”
Section: Discussionmentioning
confidence: 96%
“…This quantification was undertaken by Ion Exchange Capacity (IEC) method through pH-metric titration using calcium acetate [21]. Each sample was dried 16 hours at 60°C before titration.…”
Section: Free Cooh Groups Quantificationmentioning
confidence: 99%